The Breadth of Child Poverty in Europe: An Investigation into Overlap of Deprivations. Issue 4 (December 2013) - Roelen, Keetie; Notten, Geranda
<x xml:space="preserve">Abstract</x> Moral, efficiency, and rights‐based arguments have sparked widespread acknowledgment in both academic and policy circles that children deserve a special focus in poverty measurement. Children can be considered to have a "differential experience" of poverty in childhood, setting their situation apart from adults as well as from other children depending on their life stage. The European Union (EU) is among those bodies that have recognized the need for child‐focused indicators in monitoring poverty and social exclusion and is currently in the process of developing, testing, and comparing single indicators of child well‐being across member states. In this article, we seek to add to this debate by providing a micro‐analysis of the breadth of child poverty in the EU by analyzing the overlap of deprivations across monetary and multidimensional indicators of poverty. Thereby, we aim to gain insight into the breadth of child poverty and degree of overlap between measures of monetary and multidimensional poverty in the EU. Particular attention will be paid to the investigation of cross‐country and cross‐domain differences. Using the 2007 wave of the EU‐SILC data, we compare the EU monetary "at‐risk‐of‐poverty" indicator to a range of child deprivation indicators at the domain level in four EU member states (Germany, France, the Netherlands, and the United Kingdom). Overall, the article's findings provide a strong call for the need to take a multidimensional approach toward the measurement of child poverty in the EU context. Size and group differences between children faced with income poverty and/or deprivation in other domains are considerable and underline the need to take a broader perspective to identify those who are vulnerable. Overlap analysis of income and domain poverty suggests considerable mismatch across the board, regardless of the particular country under consideration. This suggests a considerable breadth of child poverty in the EU, meaning that deprivation in monetary and non‐monetary terms does not seem to be concentrated on a few particular groups but rather spread out across the population, with large numbers of children likely to face deprivation in a few domains. Although dependent on the domain and country under consideration, single parenthood, living in a rented dwelling, low work intensity, and income poverty are found to be significantly and considerably the risk to poverty.